THE DETERMINANTS TO PURSUE CAREER AS CHARTERED ACCOUNTANTS AMONG BUMIPUTERA ACCOUNTING UNDERGRADUATES – A CONCEPTUAL FRAMEWORK - Puvaneswari Veloo; Nor Haliza Che Hussain; Nur Raihana Mohd Sallem; Siti Nasuha Muhmad (Journal of Islamic, Social, Economics and Development, 2024)
Globalization, technological advancements, and increased in number of graduates has intensified job competition, making it crucial to add value and choose the right career path for success. The field of chartered accountancy faces shortage of professionals in many countries, including Malaysia, despite the challenging job market. Efforts are being made to increase the number of certified Bumiputera accountants in Malaysia, with a target of reaching 30 percent by 2030, however the progress has been slow, with less than 10 percent achieving certification as of now. Hence, the purpose of this paper is to identify the determinants that influence career path as chartered accountant among Bumiputera accounting undergraduates in Malaysia. This article provides a conceptual framework to establish a foundation for future research to empirically examine whether financial award, work environment, social values, market factors, and career exposure influence Bumiputera accounting undergraduates to pursue career as chartered accountants in Malaysia.